2018
DOI: 10.1111/cobi.13210
|View full text |Cite
|
Sign up to set email alerts
|

Frog occupancy of polluted wetlands in urban landscapes

Abstract: Urban sprawl and the rising popularity of water-sensitive urban design of urban landscapes has led to a global surge in the number of wetlands constructed to collect and treat stormwater runoff in cities. However, contaminants, such as heavy metals and pesticides, in stormwater adversely affect the survival, growth, and reproduction of animals inhabiting these wetlands. A key question is whether wildlife can identify and avoid highly polluted wetlands. We investigated whether pond-breeding frogs are attempting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 64 publications
(86 reference statements)
1
14
0
Order By: Relevance
“…Our results are similar to the majority of surveys conducted within the northern hemisphere (predominantly North America and Europe) that found frog species richness to be higher or equal in artificial, restored waterbodies (reviewed by Brown et al 2012). Frog assemblage patterns in waterbodies are not consistent, however, and previous Australian studies have reported variable patterns in species richness within and among both natural and constructed waterbodies (Hazell et al 2004;Lemckert and Mahony 2010;Smallbone et al 2011;Hamer et al 2012;Sievers et al 2018).…”
Section: Frog Assemblagessupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are similar to the majority of surveys conducted within the northern hemisphere (predominantly North America and Europe) that found frog species richness to be higher or equal in artificial, restored waterbodies (reviewed by Brown et al 2012). Frog assemblage patterns in waterbodies are not consistent, however, and previous Australian studies have reported variable patterns in species richness within and among both natural and constructed waterbodies (Hazell et al 2004;Lemckert and Mahony 2010;Smallbone et al 2011;Hamer et al 2012;Sievers et al 2018).…”
Section: Frog Assemblagessupporting
confidence: 83%
“…This habitat loss could be compensated for by modified or anthropogenic waterbodies (e.g. Mazerolle et al 2006;Ruhí et al 2012), with several amphibian species within Australia (Hazell et al 2004;Sievers et al 2018), North America (Monello and Wright 1999;Brand and Snodgrass 2010;Brown et al 2012) and Europe (Rannap et al 2009;Brown et al 2012;Ruhí et al 2012;Magnus and Rannap 2019) utilising anthropogenic or modified waterbodies that were either specifically designed to compensate for habitat loss or were opportunistically used by amphibians. However, species assemblages and richness can differ between anthropogenic/modified and natural waterbodies (Hazell et al 2004;Magnus and Rannap 2019), potentially due to differences in environmental factors that influence amphibian species distributions within waterbodies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some ponds are created specifically for trapping pollutants, and therefore, the presence of pollutants in these ponds is inevitable and demonstrates they function adequately. However, management actions to discourage wildlife from using highly polluted ponds may be appropriate in some cases, particularly where threatened species are present (Sievers et al 2018c). The usual management measures to reduce pollution can be undertaken (e.g., management of the water source and of the catchment area) at ponds that are managed specifically for their aesthetic values and their biodiversity.…”
Section: Water Qualitymentioning
confidence: 99%
“…Therefore, ponds in urban areas could make an important contribution to freshwater conservation, although little is known of their role as refuges (Chester and Robson 2013), or about how to maximize conservation management in these waterbodies . Some type of ponds, if not properly managed or if polluted, can nevertheless also act as ecological traps that increase the extinction risk of some populations , Sievers et al 2018c.…”
Section: Introductionmentioning
confidence: 99%
“…Animals use environmental cues (e.g., vegetation, temperature, and pH) to select habitats that maximize their fitness [129]. Constructed wetlands can provide such cues, while at the same time being unrepresentative of habitat quality, and wrongly attracting animals to these engineered systems [130,131]. High concentrations of several pollutants have been identified as an ecological trap for some species of fish and frogs in CWs, reducing their survival and impairing their growth [132,133].…”
Section: Cws May Become An 'Ecological Trap'mentioning
confidence: 99%